Branding Strategy Based on Mangrove Conservation Ecotourism-Three Colors of South Malang District - Teguh Priyo Sadono (PT Inovasi Pratama Internasional, 2024)
Currently, tourism development in East Java is running quite rapidly, especially South Malang district which has an increase in the percentage increase as of October 2023 of 59.80 % . This value increased by 1.57% from the previous month . Tourism destinations are dominated by natural tourism in the form of beaches along the Southern Cross Route, causing local communities and the government to use these beaches as tourist destinations. South Malang Regency has 101 beaches that have been opened or are still under development and several locations are still known as pristine tourist locations . From several cases of opening beach tourism locations in South Malang Regency, complaints from visitors or prospective visitors were regarding access to ingress and egress roads, conditions and behavior of the local community as well as the lack of supporting public facilities and this was also the same as expressed by tourism managers. This shows the lack of strength and unpreparedness of a brand built by regional and central governments at a coordinated tourist location . In building and developing a tourist destination brand, CMC Tiga Warna creates the identity of their tourist destination in the form of a sustainable tourism system, offering several attractions such as banana boats, canoes, snorkeling, diving and mangrove planting. By using direct and indirect marketing processes and involving customers as a supporting force in forming an image for potential visitors, CMC Tiga Warna combines marketing strategies and a strong self-identity to introduce potential visitors and the public .